Isolation and characterization of lactic acid bacteria from gastrointestinal tract of snakehead (channa striatus, bloch) as probiotic for freshwater fish - Allameh, Seyed Kamaleddin (2012)
The intensive application of antibiotics to prevent and control the bacterial diseases in aquaculture has resulted in development of antibiotic-resistant bacteria. Therefore, probiotics as an alternative strategy have been suggested to be used as replacement for antimicrobial drugs and growth promoters. Lactic acid bacteria (LAB) constitute a group of G+ve bacteria with a high ability to produce antibacterial compounds and improve fish performance which makes them excellent probiotics. In the present study, snakehead (Channa striatus), an indigenous commercial freshwater fish in Southeast Asia countries was chosen for the isolation of LAB. Isolates obtained on de Man Rogosa and Sharp (MRS) agar and broth showed 27 and 9 pure isolates from the fingerling and adults fishes, respectively. According to the antagonistic plate test against Aeromonas hydrophila as a main freshwater fish pathogen, five LABs i.e. three isolates from the fingerlings and two from the adults that showed the greatest inhibition zone were selected. The selected LABs were identified as Aerococcus viridans, Lactobacillus delbreuckii sp. delbreuckii and Enterococcus faecalis from fingerlings and Lactobacillus fermentum and Leuconostoc mesenteroides sp.mesenteroides from adult fish. Probiotic property evaluation of LAB candidates showed that they could survive and grow at pH 3 up to 8 (P < 0.05). They could also tolerate bile salt concentrations from 0.0 to 0.3% (P < 0.05). The LABs were active at different levels of NaCl (0.0 to 4%) and also, at various temperatures ranging from 15 oC to 45 oC, but showed no growth at 10 oC and 50 oC. Antagonistic effects against three tested fish pathogens i.e. A. hydrophila, Pseudomonas aeruginosa and Shewanella putrefaciens indicated that En. faecalis, L. fermentum and Leu. mesenteroides sp. mesenteroides had the highest inhibition activities. The antibiotic sensitivity test showed that En. faecalis had more antibiotic’s resistance property against some antibiotics as compared to other LAB (P < 0.05). According to probiotic characterization as screening, En. faecalis, L. fermentum and Leu. mesenteroides were selected for in vivo experiments. The viability of LABs in feed stored at 4 oC was higher than 25 oC during four weeks storage.Significant increased of the LAB proportion was observed in the fish intestine fed LAB-fortified diets as compared to the control group (P < 0.05). In addition, the lower G-ve bacteria population in the fish intestine was observed for experimental groups as compared to the control group. Effects of mono and multi-species of LAB candidates on the body composition of Javanese carp (Puntius gonionotus) indicated that LAB-fortified diets could not seriously affect the chemical composition of experimental fish carcasses. The survivability was the same for all experimental groups. The concentration of 107 cfu/g diets was overall more effective than 105 and 109 cfu/g diets. The use of En.faecalis as probiotic had more positive effects than L. fermentum and Leu.mesenteroides on growth, feed conversion ratio, specific growth rate, and protein efficiency ratio (P < 0.05). Moreover, the use of En. faecalis resulted in an increase in the production of protease and lipase enzymes in the digestive tract of Javanese carp. Results obtained from the short chain fatty acid determination which included acetate, propionate and butyrate showed that treated group with En. faecalis could significantly (P < 0.05) enhance the propionate and butyrate production as compared to the control. An in vivo challenge test of A. hydrophila as a fish pathogen with En. faecalis as a probiotic on Javanese carp indicated that this probiotic could protect the fish against A. hydrophila and showed a higher survivability compared to the control. The presence of En. faecalis in the diet could affect immune response to enhance the antibody level as a humoral response. The fish treated with a LAB-fortified diet (En. faecalis) and added pathogen (A. hydrophila) into the water showed the highest antibody level as compared to the control group (P > 0.05). In conclusion, LABs can be normal microbiota in the gastrointestinal tract of the snakehead. In addition, the use of En. faecalis as a probiotic had positive effects on overall fish performance, digestive enzymes and short chain fatty acid production, survivability in challenge with pathogen and increased humoral immune response in Javanese carp. This LAB as an environmental friendly agent can be suggested as an alternative to antibiotics in freshwater fish culture.